Entrepreneurship as an Alternative for the Labor Insertion of Trans People: A Case Study in the City of Tijuana - de la Cruz Grisdel; Fuentes Roberto; Flores Yadira; Mosqueda José (SHS Web of Conferences)
This document posits that inclusive social innovation can effectively drive sustainable regional development. Its primary goal is to assess the feasibility of a social business model designed to cultivate the entrepreneurial capabilities of transgender communities and foster their economic empowerment. The underlying assumption is that entrepreneurial training can significantly enhance the financial independence of these communities and, subsequently, their overall well-being. A case study conducted in Tijuana involved the analysis of 103 surveys from individuals who identify as transgender. The study’s key findings reveal that workplace discrimination significantly impedes their job prospects and tenure, compelling them to seek alternative sources of income. The respondents expressed a keen interest in entrepreneurship but emphasized the need for inclusive entrepreneurship training. These findings illuminate untapped opportunities for research, collaboration, and project development from an underexplored entrepreneurial standpoint.